IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) USED MOTORCYCLE DEPARTMENT DALAM MENINGKATKAN CITRA PT. SUMMIT OTO FINANCE - FIRDAUS, FERRIANSYAH (Jurnal Visi Komunikasi, 2016)
Corporate Social Responsibility (CSR) is a program that held by the company as a form of social or environmental responsibility. UMC Dept of PT Summit Oto Finance do the CSR programs to establish good relations with the public and dealers. CSR program is handled by some sections, namely UMC Dept. Head, UMC Staff, Branch Manager and Marketing Head.The purpose of this report is to investigate the preparation, implementation and evaluation of Corporate Social Responsibility (CSR) UMC Department to improve the image of PT Summit Oto Finance. The concept of this research is public relations, corporate social responsibility and corporate image. This study used a qualitative approach with case study method. The data obtained by using observation, library research and in-depth interviews of key informants. The results of this study discusses the UMC Dept. CSR program in improving the image of PT Summit Oto Finance are divided into three stages, namely the preparation and planning stages, stages of implementation and evaluation stages. These three stages are carried out by the HO (head office) that UMC Dept. Head and Staff and from the branch are Branch Manager and Marketing Head. The conclusion of this report is the CSR program UMC held on July 22, 2014. The three stages are performed optimally for results that have been planned, namely to establish good relations with the community and dealers as well as increasing the image that has been built. Tanggung Jawab Sosial Perusahaan (CSR) adalah program yang diselenggarakan oleh perusahaan sebagai bentuk tanggung jawab sosial atau lingkungan. UMC Dept dari PT Summit Oto Finance melakukan program CSR untuk menjalin hubungan baik dengan masyarakat dan dealer. Program CSR ditangani oleh beberapa bagian, yaitu Kepala Dept UMC, Staf UMC, Branch Manager dan Marketing Head. Tujuan dari laporan ini adalah untuk mengetahui persiapan, pelaksanaan dan evaluasi Tanggung Jawab Sosial Perusahaan UMC untuk memperbaiki citra. Dari PT Summit Oto Finance. Konsep penelitian ini adalah hubungan masyarakat, corporate social responsibility dan corporate image. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data diperoleh dengan menggunakan observasi, penelitian kepustakaan dan wawancara mendalam terhadap informan kunci. Hasil penelitian ini membahas program CSR UMC Dept dalam meningkatkan citra PT Summit Oto Finance yang terbagi dalam tiga tahap, yaitu tahap persiapan dan perencanaan, tahapan pelaksanaan dan tahap evaluasi. Ketiga tahapan tersebut dilakukan oleh HO (kantor pusat) bahwa Kepala Staf dan Kepala UMC dan cabang adalah Branch Manager and Marketing Head. Kesimpulan dari laporan ini adalah program CSR UMC yang diselenggarakan pada 22 Juli 2014. Ketiga tahapan tersebut dilakukan secara optimal untuk hasil yang telah direncanakan, yaitu untuk menjalin hubungan baik dengan masyarakat dan dealer serta meningkatkan citra yang telah dibangun.